Hubungan Antara Interaksi Sosial Dengan Kepercayaan Diri Pada Siswa SMK Perbankan Riau - Lola Yorissa; Syariful (LPPM Universitas Proklamasi 45, 2025)
This study aims to find out empirically the relationship between social interaction and students confidence in vocational high school banking Riau. The hypothesis is that there is a positive relationship between social interaction and students confidence in vocational high school banking Riau. This means that the higher the social interaction, the higher the self-confidence. Vice versa, the lower the social interaction, the lower the self-confidence. The subjects in this study were 100 subjects of middle adolescent age 15-18 years. The sampling technique used is a purposive sample using a social interaction scale and a self-confidence scale. Based on the data analysis, the correlation coefficient value was 0.625 with p value = 0.000 (p <0.01), meaning that there was a significant positive the relationship between social interaction and students confidence in vocational high school banking Riau.